Significance of color for a theatrical play Favorite (Journal of the College of Basic Education, 2022)
Color is an important and even essential element in the theatrical performance as it develops within females.The visual, rhythmic, psychological and social display of its many indications in the collective structures in societyLikewise, in the aesthetic values ​​that the theatrical show highlights as significant, either iconographic, allegorical, orsymbolic, and may lead to a full meaning of significance according to the specificity of (now and here), just as it is in time